Comparative forelimb myology and muscular architecture of a juvenile Malayan tapir (Tapirus indicus) - MacLaren, Jamie A. (J Anat, 2019)
The absence of preserved soft tissues in the fossil record is frequently a hindrance for palaeontologists wishing to investigate morphological shifts in key skeletal systems, such as the limbs. Understanding the soft tissue composition of modern species can aid in understanding changes in musculoskeletal features through evolution, including those pertaining to locomotion. Establishing anatomical differences in soft tissues utilising an extant phylogenetic bracket can, in turn, assist in interpreting morphological changes in hard tissues and modelling musculoskeletal movements during evolutionary transitions (e.g. digit reduction in perissodactyls). Perissodactyls (horses, rhinoceroses, tapirs and their relatives) are known to have originated with a four‐toed (tetradactyl) forelimb condition. Equids proceeded to reduce all but their central digit, resulting in monodactyly, whereas tapirs retained the ancestral tetradactyl state. The modern Malayan tapir (Tapirus indicus) has been shown to exhibit fully functional tetradactyly in its forelimb, more so than any other tapir, and represents an ideal case‐study for muscular arrangement and architectural comparison with the highly derived monodactyl Equus. Here, we present the first quantification of muscular architecture of a tetradactyl perissodactyl (T. indicus), and compare it to measurements from modern monodactyl caballine horse (Equus ferus caballus). Each muscle of the tapir forelimb was dissected out from a cadaver and measured for architectural properties: muscle‐tendon unit (MTU) length, MTU mass, muscle mass, pennation angle, and resting fibre length. Comparative parameters [physiological cross‐sectional area (PCSA), muscle volume, and % muscle mass] were then calculated from the raw measurements. In the shoulder region, the infraspinatus of T. indicus exhibits dual origination sites on either side of the deflected scapular spine. Within ungulates, this condition has only been previously reported in suids. Differences in relative contribution to limb muscle mass between T. indicus and Equus highlight forelimb muscles that affect mobility in the lateral and medial digits (e.g. extensor digitorum lateralis). These muscles were likely reduced in equids during their evolutionary transition from tetradactyl forest‐dwellers to monodactyl, open‐habitat specialists. Patterns of PCSA across the forelimb were similar between T. indicus and Equus, with the notable exceptions of the biceps brachii and flexor carpi ulnaris, which were much larger in Equus. The differences observed in PCSA between the tapir and horse forelimb muscles highlight muscles that are essential for maintaining stability in the monodactyl limb while moving at high speeds. This quantitative dataset of muscle architecture in a functionally tetradactyl perissodactyl is a pivotal first step towards reconstructing the locomotor capabilities of extinct, four‐toed ancestors of modern perissodactyls, and providing further insights into the equid locomotor transition.